Spliceostatin A interaction with SF3B limits U1 snRNP availability and causes premature cleavage and polyadenylation. Issue 9 (16th September 2021) - Yoshimoto, Rei; Chhipi-Shrestha, Jagat K.; Schneider-Poetsch, Tilman; Furuno, Masaaki; Burroughs, A. Maxwell; Noma, Shohei; Suzuki, Harukazu; Hayashizaki, Yoshihide; Mayeda, Akila; Nakagawa, Shinichi; Kaida, Daisuke; Iwasaki, Shintaro; et al.
Summary: RNA splicing, a highly conserved process in eukaryotic gene expression, is seen as a promising target for anticancer agents. Splicing is associated with other RNA processing steps, such as transcription and nuclear export; however, our understanding of the interaction between splicing and other RNA regulatory mechanisms remains incomplete. Moreover, the impact of chemical splicing inhibition on long non-coding RNAs (lncRNAs) has been poorly understood. Here, we demonstrate that spliceostatin A (SSA), a chemical splicing modulator that binds to the SF3B subcomplex of the U2 small nuclear ribonucleoprotein particle (snRNP), limits U1 snRNP availability in splicing, resulting in premature cleavage and polyadenylation of MALAT1, a nuclear lncRNA, as well as protein-coding mRNAs. Therefore, truncated transcripts are exported into the cytoplasm and translated, resulting in aberrant protein products. Our work demonstrates that active recycling of the splicing machinery maintains homeostasis of RNA processing beyond intron excision. Graphical abstract: Highlights: SSA generates a prematurely polyadenylated short isoform of MALAT1 SSA inhibits the recycling of U1 snRNP on pre-mRNAs and reduces the available pool A subset of mRNAs are prematurely cleaved and polyadenylated The truncated mRNAs are subjected to translation in the cytoplasm Abstract : Yoshimoto et al. demonstrated that spliceostatin A (SSA), a splicing modulator targeting the U2 snRNP, retards U1 snRNP recycling from mRNA and leads to premature cleavage and polyadenylation of MALAT1, a long non-coding RNA, as well as other mRNAs. The aberrant mRNAs become a source of truncated proteins.